A practical, rapid generation-advancement system for rice breeding using simplified biotron breeding system - Tanaka, Junichi (Breeding science, 2016)
A new plant breeding method-the biotron breeding system (BBS)-can rapidly produce advanced generations in rice (Oryza sativa L.) breeding. This method uses a growth chamber (biotron) with CO2 control, accompanied by tiller removal and embryo rescue to decrease the period before seed maturity. However, tiller removal and embryo rescue are laborious and impractical for large populations. We investigated the influences of increased CO2, tiller removal, and root restriction on the days to heading (DTH) from seeding in growth chambers. The higher CO2 concentration significantly decreased DTH, but tiller removal and root restriction had little effect on DTH and drastically reduced seed yield. Based on these findings, we propose a simplified BBS (the sBBS) that eliminates the need for tiller removal and embryo rescue, but controls CO2 levels and day-length and maintains an appropriate root volume. Using the sBBS, we could reduce the interval between generations in 'Nipponbare' to less than 3 months, without onerous manipulations. To demonstrate the feasibility of the sBBS, we used it to develop isogenic lines using 'Oborozuki' as the donor parent for the low-amylose allele Wx1-1 and 'Akidawara' as the recipient. We were able to perform four crossing cycles in a year